Externalism, Relational Selves, and Redemptive Relationships - Teske, John A. (Zygon, 2011)
Abstract. The dangerous level of individuality in contemporary Western culture is informed by a conception of mind, self, and soul as internal to the central nervous system. The historical development of this view has produced a bounded and self-contained individual at odds with communal life. Happily, scientific and philosophical studies of mind are coming to view the human mind as embodied, enactive, encultured, and embedded in social and technical networks, and as a construction not limited to the boundaries of the individual organism. Mental phenomena are hybrids of events in the head and events in the world to which they are often coupled, not least of which are with other people. There are mutual and reciprocal implications of this externalism for a number of religious themes. Our understanding of redemption might better be bound to our relationships with others, including our bodies and our sexuality, rather than to a private, individual relationship with the sacred.